Single-shot electrons and protons time-resolved detection from high-intensity laser–solid matter interactions at SPARC_LAB. (2019) - Bisesto, F.; Galletti, M.; Anania, M. P.; Ferrario, M.; Pompili, R.; Botton, M.; Zigler, A.; Consoli, F.; Salvadori, M.; Andreoli, P.; Verona, C.
Abstract : Laser–plasma interactions have been studied in detail over the past twenty years, as they show great potential for the next generation of particle accelerators. The interaction between an ultra-intense laser and a solid-state target produces a huge amount of particles: electrons and photons (X-rays and $\unicode[STIX]{x03B3}$ -rays) at early stages of the process, with protons and ions following them. At SPARC_LAB Test Facility we have set up two diagnostic lines to perform simultaneous temporally resolved measurements on both electrons and protons.